2019
DOI: 10.1021/acs.biomac.9b01021
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically Strong, Heat-Resistant, Water-Induced Shape Memory Poly(vinyl alcohol)/Regenerated Cellulose Biocomposites via a Facile Co-precipitation Method

Abstract: In this work, poly(vinyl alcohol) (PVA) biocomposites with regenerated cellulose-softwood pulp (RC-SP) as a green reinforcement were prepared via coprecipitation method. Simultaneous precipitation of the two components promotes uniform dispersion of the RC-SP and constructs strong molecular chain entanglements and hydrogen bonding network inside the composites. This physical cross-linking network reduces the water absorption and improves the water resistance of the composites. The incorporation of RC-SP not on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…A synergistic mechanism can explain the strong adhesion between SCGC films and various substrates due to the formation of noncovalent cross-links, including dynamic hydrogen bonding and electrostatic attraction. In addition, the entangled physical network and the constructed hydrogen bond network inside the film form a stable structure, which hinders the penetration of external water molecules to a certain extent to maintain the internal structural stability of the SCGC composite film. , The adhesion of SCGC under liquid nitrogen was studied, and the SCGC film could maintain a specific viscosity even at low temperatures. It was found that weights stuck with SCGC in liquid nitrogen took 138 s to separate from each other (Figure n and Video S1) and that SCGC regained its stickiness less than 30 s after leaving the liquid nitrogen, offering the possibility of its use as an adhesive at low temperatures (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…A synergistic mechanism can explain the strong adhesion between SCGC films and various substrates due to the formation of noncovalent cross-links, including dynamic hydrogen bonding and electrostatic attraction. In addition, the entangled physical network and the constructed hydrogen bond network inside the film form a stable structure, which hinders the penetration of external water molecules to a certain extent to maintain the internal structural stability of the SCGC composite film. , The adhesion of SCGC under liquid nitrogen was studied, and the SCGC film could maintain a specific viscosity even at low temperatures. It was found that weights stuck with SCGC in liquid nitrogen took 138 s to separate from each other (Figure n and Video S1) and that SCGC regained its stickiness less than 30 s after leaving the liquid nitrogen, offering the possibility of its use as an adhesive at low temperatures (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…[ 88 ] Copyright 2017, American Chemical Society; memory material: Reproduced with permission. [ 30 ] Copyright 2019, American Chemical Society; gel electrolyte: Reproduced with permission. [ 29 ] Copyright 2020, Springer Nature; mesoporous membrane: Reproduced with permission.…”
Section: Molecular Design Strategy For Cellulose‐based Functional Matmentioning
confidence: 99%
“…[4] Meanwhile, nanomaterials such as conductive polymer sheets, metal oxide nanoparticles, 2D covalent layers, and responsive polymer molecules, can be well-integrated with cellulose macromolecules during self-assembly processes to create functional materials with conductive, magnetic, electrochemical, and stimuli responsiveness. [28][29][30][31] These properties offer huge opportunities for creating cellulose materials, such as transparent substrates, flexible conductors, electronic-ionic gels, electrolytes, and dielectric layers, in flexible sensors, conductive transistors, supercapacitors, optoelectronic devices, and bioelectronics. [29,[32][33][34][35][36][37][38][39][40] In this review, we discuss the properties of cellulose and green dissolution systems.…”
Section: Introductionmentioning
confidence: 99%
“…Shape memory materials have been reported for various applications in biomedicine [1], packaging [2], actuation [3] (particularly in soft robots [4]), and flexible electronic devices [5]. Materials' shapes can be programmed and recovered by external stimuli such as light [6][7][8][9], heat [2,5,10], magnetic fields [11], water [12][13][14], pH [3,15], or combination(s) of multiple stimuli [4,[16][17][18][19]. One-way shape memory effects using heat to program the material shape is of interest due to its simplicity.…”
Section: Introductionmentioning
confidence: 99%